Pengaruh Pemberian Silase Pakan Komplit Berbasis Sorghum Clitoria Ternatea dengan Penambahan Konsentrat Mengandung ZnSO4 Dan Zn-Cu Isoleusinat Terhadap Konsumsi dan Kecernaan Fraksi Serat Pada Kambing Kacang - Moruk, Aderitus Agustinus; Hartati, Erna; Lestari, Gusti Ayu Y. (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this study was to determine the effect of complete feeding of sorghum-Clitoria ternatea silage with the addition of various levels of concentrates containing ZnSO4 and Zn-Cu Isoleucinate on the consumption and digestibility of ADF, NDF, and lignin in kacang goats. The materials used were 12 male kacang goats and 12 units of metabolic cages on stilts. This study used a randomized block design (RBD) which consisted of 4 treatments with 3 replications for each treatment so that there were 12 experimental units. The treatments were T0: sorghum-Clitoria ternatea silage without concentrate, T1: sorghum-Clitoria ternatea silage + 10% concentrate containing 150 mg ZnSO4/kg DM concentrate and 2% Zn-Cu Isoleucinate/kg DM ration, T2: sorghum-Clitoria silage ternatea + 10% concentrate containing 150 mg ZnSO4/kg DM concentrate and 2% Zn-Cu Isoleucinate/kg DM ration, T3: sorghum-Clitoria ternatea silage + 10% concentrate containing 150 mg ZnSO4/kg DM concentrate and 2% Zn-Cu Isoleucinate/kg DM ration. The variables measured were ADF consumption, NDF consumption, lignin consumption, ADF digestibility, NDF digestibility, and lignin digestibility. The data collected in this study were tabulated and analyzed using analysis of variance. The results of statistical analysis showed that the treatment had a significant effect (P<0.05) on lignin digestibility and had no significant effect (P>0.05) on ADF consumption, ADF digestibility, NDF consumption, NDF digestibility and lignin consumption. It was concluded that the complete feeding based on sorghum-Clitorea ternatea silage with the addition of concentrate containing ZnSO4 and Zn-Cu Isolesuinate had an effect on increasing lignin digestibility and giving the same results on ADF consumption, ADF digestibility, NDF consumption, NDF digestibility and lignin consumption in kacang goats.